Understanding vineyard soils - White, R. E. (Robert Edwin), 1937- (Oxford University Press, 2015)
The first edition of Understanding Vineyard Soils, published in 2009, has been praised for its comprehensive coverage of soil topics relevant to viticulture, and is a major resource for professionals in the industry. However, the subject is not static--new developments are occurring in the field all the time. For example, the 'organic movement' in viticulture continues to grow in importance and the emphasis on wine quality relevant to quantity is changing in an increasingly competitive world market. The promotion of organic and biodynamic practices has raised a general awareness about 'soil he.